EVAPOTRANSPIRATION AND IRRIGATION WATER REQUIREMENTS EVALUATION OF CHINAROK AREA USING ASCE PENMAN- MONTEITH METHOD - Al-Kazragy, M. O. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
The Koya Directorate of Irrigation (KDI) has a plan to develop the agriculture and launch new agricultural projects in Chinarok area in particular for forestry and orchards plantation. This development requires quantifying the amount of irrigation water and evapotranspiration for the vegetated area. In this paper, these requirements were investigated and evaluated. Chinarok is a rural area located in Kurdistan region north of Iraq. The (KDI) classified the area into three major vegetation types; turfgrass, orchards and forests. Based on the metrological records and plants physical properties, an evapotranspiration (ET) has to be evaluated at the drought summer season, where maximum value is expected. The ET was evaluated for the three vegetation covers by using Penman-Monteith equation which was standardized by the American Society of Civil Engineers and known as ASCE- Penman-Monteith equation which is the most reliable method in estimating ET. It was found that ET values evaluated by Penman-Monteith method showed good agreement with experimental results of ET of a published data. Irrigation water requirement in terms of depth and irrigation frequency were evaluated for the three sectors of vegetation based on soil moisture deficit. In addition, irrigation requirements were calculated in terms of volume and daily water demand. The capacity of ground storage reservoir (or storage pond) was recommended as 5400 m3 to meet daily water demand. These findings provide a base for the design and operation of proposed irrigation systems in Chinarok.